Overcoming Resistance to Checkpoint Inhibitors: Natural Killer Cells in Non-Small Cell Lung Cancer - Gemelli, Maria; Noonan, Douglas M.; Carlini, Valentina; Pelosi, Giuseppe; Barberis, Massimo; Ricotta, Riccardo; Albini, Adriana (Frontiers in Oncology, 2022)
Immune Checkpoint Inhibitors (ICIs) have revolutionized cancer treatments over the last 10 years, with even increasing indications in many neoplasms. Non-Small Cell Lung Cancer (NSCLC) is considered highly immunogenic and ICIs have found a wide set of application in this area, both in early and advanced line of treatment, significantly changing the prognosis of these patients. Unfortunately, not all patients can benefit from the treatment and resistance to ICIs can develop at any time. In addition to T-lymphocytes, which are the major target, a variety of other cells present in the tumor microenvironment (TME) acts in a complex cross-talk between tumor, stromal and immune cells. An imbalance between activating and inhibitory signals can shift TME from an “anti-” to a “pro - tumorigenic” phenotype and vice versa. Natural Killer cells (NKs) are able to recognize cancer cells, based on MHC I (self and non-self) and independently from antigen presentation. They represent an important link between innate and adaptive immune response. Little data is available about the role of pro-inflammatory NKs in NSCLC and how they can influence the response to ICIs. NK cells express several ligands of the checkpoint family, such as PD-1, TIGIT, TIM3, LAG3, CD96, IL1R8 and NKG2A. We and others have shown that TME can also shape NK cells, converting them into a pro-tumoral, pro-angiogenic “nurturing” phenotype, through “decidualization”. The features of these NK cells include expression of CD56, CD9, CD 49a and CXCR3, low CD16 and poor cytotoxicity. During ICIs therapy, tumor infiltrating or associated NKs can both respond to the inhibitors or counteract the effect acting as pro inflammatory. There is a growing interest in NKs as a promising therapeutic target, as basis for adoptive therapy and through CAR-NK technology. In this review we analyze current evidence on NKs function in NSCLC, focusing on their possible influence in response to ICIs treatment and resistance development, addressing their prognostic and predictive role and the rational for exploiting NKs as a tool to overcome resistance in NSCLC and to envisage a way to repolarize dNK-like cells in lung cancer.